Dermatoscopic and clinical features of congenital or congenital-type nail matrix nevi: a multicenter prospective cohort study by the International Dermoscopy Society - Pham, Félix; Boespflug, Amélie; Duru, Gérard; Phan, Alice; Poulalhon, Nicolas; Weiler, Laura; Tanaka, Masaru; Lallas, Aimilios; Ogata, Dai; Davaine, Anne Céline; Bahadoran, Philippe; Balguerie, Xavier; et al. (Journal of the American Academy of Dermatology, 2022)
Background - Congenital nail matrix nevi (NMN) are difficult to diagnose because they feature clinical characteristics suggestive of adult subungual melanoma. Nail matrix biopsy is difficult to perform, especially in children. - Objective - To describe the initial clinical and dermatoscopic features of NMN appearing at birth (congenital) or after birth but before the age of 5 years (congenital-type). - Methods - We conducted a prospective, international, and consecutive data collection in 102 hospitals or private medical offices across 30 countries from 2009 to 2019. - Results - There were 69 congenital and 161 congenital-type NMNs. Congenital and congenital-type NMN predominantly displayed an irregular pattern of longitudinal microlines (n = 146, 64%), reminiscent of subungual melanoma in adults. The distal fibrillar (“brush-like”) pattern, present in 63 patients (27.8%), was more frequently encountered in congenital NMN than in congenital-type NMN (P = .012). Moreover, congenital NMN more frequently displayed a periungual pigmentation (P = .029) and Hutchinson’s sign (P = .027) than did congenital-type NMN. - Limitations - Lack of systematic biopsy-proven diagnosis and heterogeneity of clinical and dermatoscopic photographs. - Conclusion - Congenital and congenital-type NMN showed worrisome clinical and dermatoscopic features similar to those observed in adulthood subungual melanoma. The distal fibrillar (“brush-like”) pattern is a suggestive feature of congenital and congenital-type NMN.